Realities and Impacts of Teaching Approach and Method in Bilingual Classroom in Indonesia - Imamatul Khair (Master Program in Linguistics, Diponegoro University, 2022)
Pedagogical approach and methods are prominent in students’ engagement in second language learning. Strategies and scaffolds are two other interconnected issues that matter in bilingual classrooms. This study crafted some findings of pedagogical practices performed by bilingual teachers which may fall into accommodating or dumbing down bilingual learners’ needs. It is an ethnographic study which used class observations as data to find the realities of practices that teachers used for English language learners at the Indonesian college level. It revealed how a teacher stood for a certain method and pedagogical approach to negotiate instructional strategies within a bilingual classroom. Further, this study picturized challenges, upsides, and downsides of using the approach and method in the bilingual classroom which needs further balance of two language acquisitions. This study implicates principles of second language teaching and learning and most importantly bilingual teaching resources are required to improve the effectiveness of bilingual teaching.